Architectures of Coloniality - Melissa Rovner (Enquiry: The ARCC Journal of Architectural Research, 2023)
The Owens Valley Paiute, traditional caretakers of the “Land of Flowing Water,” face continued threats to their livelihood due to decades of water extraction from the region by the city of Los Angeles. The precarious state of Indigenous lands and peoples across California is entangled with historical processes supported by the Bureau of Indian Affairs (BIA) and the off-reservation boarding school system. During the first half of the twentieth century, Paiute, Mission Indian and other Indigenous youth were sent to the Sherman Institute in Riverside, the last of twenty-five boarding schools to be built and operated by the BIA. Accompanying its Mission Revival style façade and the associated narratives of racial uplift, the school aimed to distance students from tribal affiliations, teaching them Anglo, heteropatriarchal forms of domesticity, and training them to become wage laborers in the farming, construction, and domestic service trades. After graduation, many students were employed by the federal government to convert tribal lands to agricultural plots and private property, while many others found low-wage, unskilled positions in the building and maintenance of Southern California’s expanding metropolis. This paper investigates the role of the Sherman Institute in the exploitation of Indigenous lands and labor for regional development, and therefore, the production of racialized precarity for Indigenous peoples. By engaging with Indigenous epistemologies, the paper works to stretch the limits of history/theory, to expose systems of confinement for their racialized underpinnings, and to introduce more fluid conceptions of land, property, and personhood.